Magic filters, poisoning, illness and medical in French literature regarding Life is a Dream by Pedro Calderon de la Barca - Jiménez, Israel (2015)
The aim of this work is to make a journey through French literature and with respect to the work Life is a Dream by Pedro Calderon de la Barca in those literary texts that refer explicitly to the magical filters, poisoning, disease and doctors through their characters from the twelfth century. The bad reputation they have had doctors because in many cases the cure was worse than the disease found in literary texts.